Enhanced photo-catalytic activity of ordered mesoporous indium oxide nanocrystals in the conversion of CO2 into methanol. Issue 8 (3rd July 2017) - Gondal, M. A.; Dastageer, M. A.; Oloore, L. E.; Baig, U.; Rashid, S. G.
ABSTRACT: Ordered mesoporous indium oxide nanocrystal ( m -In2 O3 ) was synthesized by nanocasting technique, in which highly ordered mesoporous silca (SBA-15) was used as structural matrix. X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halanda (BJH) studies were carried out on m -In2 O3 and the results revealed that this material has a highly ordered mesoporous surface with reduced grain size, increased surface area and surface volume compared to the non porous indium oxide. The diffuse reluctance spectrum exhibited substantially improved light absorption efficiency in m -In2 O3 compared to normal indium oxide, however, no considerable change in the band gap energies of these materials was observed. When m -In2 O3 was used as a photo-catalyst in the photo-catalytic process of converting carbon dioxide (CO2 ) into methanol under the pulsed laser radiation of 266-nm wavelengths, an enhanced photo-catalytic activity with the quantum efficiency of 4.5% and conversion efficiency of 46.3% were observed. It was found that the methanol production yield in this chemical process is as high as 485 µlg −1 h −1 after 150 min of irradiation, which is substantially higher than the yields reported in the literature. It is quite clear from the results that the introduction of mesoporosity in indium oxide, and the consequent enhancement of positive attributes required for a photo-catalyst, transformed photo-catalytically weak indium oxide into an effective photo-catalyst for the conversion of CO2 into methanol.